Problematics of Tematic Learning in Grade I at SDN 1 Undaan Turen During The Pandemic - Meilina, Endah; Umayaroh, Siti; Mahanani, Putri (Angstrom Centre of Education, 2024)
This study aims to describe the problematics or learning problems in terms of planning, implementation, and evaluation. This research is descriptive qualitative research. This research was conducted at SDN 1 Undaan Turen which is located at Jl. Cemara No. 5 Undaan, Turen District, Malang Regency The data collection techniques in this study include observation, interviews, and documentation. The data collection instruments used were interview sheets, documentation sheets and observation sheets. Data analysis used in this research is through the stages of data reduction, data exposure, and conclusion drawing and verification. The results showed that the problems in the planning aspect included the difficulty of managing lesson plans, learning media, preparation of learning materials, and preparation of methods. Problems in the implementation aspect include uneven internet facilities, most students cannot read and write, and limited teacher space in monitoring students. Meanwhile, problems in the evaluation aspect are that some students do not do their assignments and the assignments are not done by the students themselves.